Boldine Inhibits Mouse Mammary Carcinoma In Vivo and Human MCF-7 Breast Cancer Cells In Vitro - Tomšík, Pavel; Mičuda, Stanislav; Muthná, Darina; Čermáková, Eva; Havelek, Radim; Rudolf, Emil; Hroch, Miloš; Kadová, Zuzana; Řezáčová, Martina; Ćmielová, Jana; Živný, Pavel (Planta Medica, 2016)
Boldine is an aporphine alkaloid widely consumed in the folk medicine of some regions. Its anticancer potential has been shown but not yet elucidated. We compared the antitumor effect of orally and parenterally applied boldine in mice bearing solid Ehrlich tumor. We also explored the effects of boldine on breast adenocarcinoma MCF-7 cells in vitro. Repeated i. p. injections of 30, 60, or 90 mg boldine/kg, either alone or combined with doxorubicin, slowed tumor growth in vivo. The latter two doses also prolonged the post-therapeutic survival of the mice. When fed food supplemented with boldine at a dose of 90 mg/kg, the tumor-bearing mice survived significantly longer, but there was no effect on tumor size. Interestingly, continuous p. o. administration did not produce detectable levels of boldine in plasma or tissue samples, in contrast to high but short-lived concentrations after i. p. injections. There was neither antagonism nor synergism between boldine and doxorubicin, except a possible synergism of i. p. boldine 90 mg/kg combined with doxorubicin when compared with doxorubicin alone.Boldine was cytotoxic to MCF-7 cells and reduced their viability and proliferation in vitro. Exposure to boldine decreased bromodeoxyuridine incorporation and histone H3 phosphorylation but did not induce apoptosis. Boldine treatment resulted in p38, ERK, and JNK activation in the mitogen-activated protein kinase pathway in a dose-dependent manner. Since bioavailability in mice seems to be different from that reported in rats, pharmacokinetic studies in humans are needed to evaluate the role of boldine in the beneficial effects of Boldo infusions.
Keywords: boldine; cancer; in vivo; in vitro